iPSC-derived cells for whole liver bioengineering - Telles-Silva, Kayque Alves; Pacheco, Lara; Chianca, Fernanda; Komatsu, Sabrina; Chiovatto, Caroline; Zatz, Mayana; Goulart, Ernesto (Frontiers in Bioengineering and Biotechnology, 2024)
Liver bioengineering stands as a prominent alternative to conventional hepatic transplantation. Through liver decellularization and/or bioprinting, researchers can generate acellular scaffolds to overcome immune rejection, genetic manipulation, and ethical concerns that often accompany traditional transplantation methods, in vivo regeneration, and xenotransplantation. Hepatic cell lines derived from induced pluripotent stem cells (iPSCs) can repopulate decellularized and bioprinted scaffolds, producing an increasingly functional organ potentially suitable for autologous use. In this mini-review, we overview recent advancements in in vitro hepatocyte differentiation protocols, shedding light on their pivotal role in liver recellularization and bioprinting, thereby offering a novel source for hepatic transplantation.Finally, we identify future directions for liver bioengineering research that may allow the implementation of these systems for diverse applications, including drug screening and liver disease modeling.